A special filler for epoxy resin to enhance the T peel strength of adhesive. Issue 10 (9th August 2020) - Xu, Hang; Zhang, Xiaorui; Hu, Guangkai; Weng, Ling; Liu, Lizhu
Abstract: The filler that could enhance the T peel strength of adhesive was prepared using graphene oxide (GO) grafted with toluene diisocyanate (TDI) and amino terminated poly(butadiene‐acrylonitrile) (ATBN). As a result of structure characterization, the ATBN‐TDI‐GO structure with dissociated ‐NCO groups was built. The T peel strength of the adhesive containing 25 wt% ATBN, 17 wt% TDI, and 0.5 wt% GO increased to 18.47 N/mm, which increased by 4.75 times compared with pure epoxy resin (EP), and other mechanical properties of the adhesive were enhanced. The reason for the increasing of bonding properties was chemical bonding built between the adherent and the adhesive by the surplus ‐NCO groups provided by the ATBN‐TDI‐GO filler. The effect of physical adsorption provided by ATBN and the chemical bonding between the matrix resin and ATBN‐TDI‐GO filler also could toughen the EP resin. The design of the EP filler could provide a new method for adhesive manufacture.